Study on Factors Influencing the Viscosity of Sodium Carboxymethyl Cellulose Used in Capsule-Mucous Sealers. (29th January 2022) - Wang, Fakai; Sun, Zhongguang; Li, Xuelong; Wang, Kequan; Chen, Deyou; Li, Zhen
Abstract : A decrease in the viscosity of a solution of sodium carboxymethyl cellulose (CMC-Na) is a commonly encountered problem in coalbed methane (CBM) pressure measurement with an apron CMC-Na sealer and capsule CMC-Na sealer. Studies have shown that the factors that can reduce the CMC-Na solution viscosity include the hydrogen ion concentration index (pH), the environmental temperature, the drilling and sealing time, and the high-pressure CBM gas environment. In this study, a homemade instrument for measuring the viscosity of a CMC-Na solution under high pressure was used to determine the change laws of the viscosity under different conditions, and comparative tests were performed to investigate various factors affecting the viscosity. The best solution for stabilizing the viscosity was determined and effectively applied at a coal mine site, where an overall improvement in the viscosity behaviour was observed.